DAMPAK KEBIJAKAN TRANSHIPMENT OLEH INDONESIA PADA INDSUTRI PRODUK OLAHAN IKAN THAILAND - Djoesept Harmat Tarigan; Pradono Budi Saputro (Ensiklopedia of Journal, 2022)
The problem of transhipment is a matter of transitional transport or modified transportation issues. This transit place can receive supplies and can deliver goods. The main purpose of the transshipment problem is to minimize the cost of the distribution of goods delivered from the place of origin to the destination even though through the transit point. The problem in this research is with the policy of transhipment issued by Indonesian government causing negative impact to fishery industry, especially processed fishery product in Thailand country The eradication of fish theft in Indonesian waters had a direct impact on Thailand's fishery exports which affected the country's gross domestic product (GDP). Thailand National Economic and Social Development Board (NESDB) data reveal that the contribution of the fishery sector to Thailand's GDP has decreased drastically. The average contribution of the fishery sector to Thailand's GDP has been recorded at 1.6 percent, while in the third quarter of 2015 it contributed minus 3.1 percent. While the Ministry of Marine Affairs and Fisheries (KKP) noted in 2013 to second quarter 2014, Thai fishery industry has decreased.